Kenya: The Pioneers of Brachiaria Grass - Makila, Ethel; Njarui, Donald M.G.; Ghimire, Sita R. (International Livestock Research Institute, 2017)
An interview by Ethel Makila (ILRI-Beca) with Donald Njarui (KALRO/Kenya) and Sita Ghimire (ILRI-Beca, Kenya) in Nairobi at International Livestock Research Institute (ILRI) in Nairobi/Kenya. Recorded on Nov. 11, 2017